Analysis of the Microbiological data from the Omadacycline (OMC) Phase 3 Community-Acquired Bacterial Pneumoniae (CABP) trial: The OPTIC study. (4th October 2017) - Armstrong, Eliana; Tzanis, Evan; Manley, Amy; McGovern, Paul; Das, Anita; Steenbergen, Judith N
Abstract: Background: OMC is a novel aminomethylcycline antibiotic that completed Phase 3 studies as once daily oral and intravenous (IV) monotherapy for CABP (OPTIC study) and acute bacterial skin and skin structure infections (OASIS study). CABP is a common, serious infection, in which microbiological confirmation of infection is difficult and a pathogen is only identified in <10% of patients. The OPTIC study demonstrated that OMC was non-inferior to MOX at the post treatment evaluation in the microbiological intent-to-treat (microITT population) (89.2 vs. 87.4; 95% CI: -4.6, 8.5). Methods: The microITT population consisted of subjects in the ITT population who had at least 1 causative pathogen identified at screening through positive blood culture, adequate quality lower respiratory tract culture, positive urinary antigen for Legionella pneumophila or Streptococcus pneumoniae, or positive serology titers for L. pneumophila, Mycoplasma pneumoniae or Chlamydophila pneumoniae . Results: Requiring a microbiological diagnosis in the OPTIC study resulted in 49.8% (386/774) of the ITT qualifying for inclusion in the microITT. By culture methods, 24.1% had a Gram-positive pathogen, 38.1% had a Gram-negative pathogen and the majority were mono-microbial. The most frequently isolated pathogens from culture in the microITT were S. pneumoniae (13.7%), H. influenzae (12.4%), H. parainfluenzae (9.1%), Klebsiella pneumoniae (6.7%) and S. aureus (5.7%). In total, 28.3% (15/53) and 24.5% (13/53) of S. pneumoniae were macrolide resistant and multi-drug resistant, respectively. Serotype 3 was the most common S. pneumoniae serotype. There was no correlation between OMC MIC values and clinical outcome which suggests that target exposures were achieved at the infection site. Conclusion: OMC is a novel antibiotic with potent in vitro and clinical activity against typical and atypical CABP pathogens, including multi-drug resistant S. pneumoniae . Disclosures: E. Armstrong, Paratek Pharmaceuticals: Consultant, Consulting fee; E. Tzanis, Paratek Pharmaceuticals: Employee and Shareholder, Salary; A. Manley, Paratek Pharmaceuticals: Employee and Shareholder, Salary; P. McGovern, Paratek Pharmaceuticals: Employee and Shareholder, Salary; A. Das, Paratek Pharmaceuticals: Employee and Shareholder, Salary; J. N. Steenbergen, Paratek Pharmaceuticals: Employee and Shareholder, Salary